Knowledge, attitude and practice of Chinese medical staff in early pulmonary rehabilitation during acute exacerbation of chronic obstructive pulmonary disease: a cross-sectional study - Yan Liu; Li Yao; Yaling Li; Tingshu Wang; Tingrui Wang; Zhangyi Wang; Fangrong Jia; Pe Cai; Qinqin Li; Yuhan Chen (BMJ Open)
Objective To investigate the knowledge, attitude and practice (KAP) of early pulmonary rehabilitation (PR) of acute exacerbation of chronic obstructive pulmonary disease (AECOPD) among Chinese medical staff and the relationship between them.Design A multicentre cross-sectional survey was used in this study.Setting The study was conducted at multiple hospitals in Guizhou Province, China.Participants A total of 745 medical staff were recruited from several hospitals in Guizhou Province by convenient sampling method.Primary and secondary outcome measures A 41-item questionnaire was used to collect the demographic characteristics of the respondents and the KAP of the medical staff on the early PR of AECOPD.Results The average KAP scores were 64.49±17.24, 42.81±5.95 and 41.39±8.97. There were significant positive correlations between knowledge and attitude (r=0.491, p<0.001), knowledge and practice (r=0.129, p<0.001), and attitude and practice (r=0.246, p<0.001). Medical staff with prior PR training and AECOPD early PR experience had higher knowledge and practice scores. Attitudes were significantly influenced by gender, hospital level, professional title and respiratory staff status, while practice scores were significantly affected by prior experience, knowledge and patient contact frequency.Conclusions The study found that medical staff’s knowledge and attitudes affect their practices, and experience and education influence their knowledge. It suggests that organisations should enhance education and training to improve medical staff’s knowledge and attitudes, thus enhancing clinical practice. However, the study’s focus on Guizhou Province and the high number of nurses in the sample may limit the generalisability of the results.